Implementasi Strategi Pembelajaran Multiple Intelligences pada Mata Pelajaran PAI Studi Kasus di SD Semai Jepara - Santi Andriyani; Abdulloh Hamid (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract:This research is aimed at finding out : (1) the implementation of learning strategy of multiple intelligences in Islamic education lesson at SD Semai Jepara ; (2) the factors that affect the implementation of learning strategy of multiple intelligences in Islamic education lesson at SD Semai Jepara. This research uses Case Study Method. The techniques used in collecting the data are interview, observation, and documentation. The results of this research showed that : (1) The learning of PAI with the matery â€œAl Kautsarâ€is using parody and reading aloud strategies and (2) the factors that affect in implementating the learning strategy of multiple intelligences in Islamic education lesson at SD Semai Jepara are; teacher, student, infrastructure, and environment aspects .Keywords: Islamic Education, Multiple Intelligences, Case Study.